Anti-obesity effect of Angelica keiskei Jiaosu prepared by yeast fermentation on high-fat diet-fed mice - Fu, Kunli; Gao, Xiang; Hua, Puyue; Huang, Yuedi; Dong, Ruitao; Wang, Mingji; Li, Qun; Li, Zichao (Frontiers in Nutrition, 2023)
In this study, an Angelica keiskei (A. keiskei) Jiaosu (FAK) was prepared by yeast fermentation to investigate its anti-obesity effect on high-fat diet-fed mice. 70 SPF grade male C57BL/6J mice were randomly divided into 7 groups (n=10): blank control group (N), high-fat model group (M), positive control group (Orl), unfermented control group (NF), high-dose intervention group (FH), medium-dose intervention group (FM), and low-dose intervention group (FL). The results showed that FAK intervention significantly reduced the body weight, Lee's index and liver index of high-fat diet-fed mice (P<0.05). Compared with M group, the serum levels of triglyceride (TG), total cholesterol (TC), leptin and glucose (GLU) in FH group were remarkably decreased and that of interleukin-27 (IL-27) were increased (P<0.05). The levels of TG, and TC in the liver of mice were also markedly decreased in the FH group (P<0.05). HE staining results showed that the liver cells in the three intervention groups had less degeneration and fatty vacuoles in the cytoplasm, and the liver cords were orderly arranged compared with that of M group. Furthermore, FAK significantly inhibited epididymal adipose tissue cell expansion induced by high-fat diet. FAK up-regulated the protein expression levels of p-AMPK and PPARα to promote lipolysis and down-regulated the expression of PPARγ to reduce lipid synthesis (P<0.05). Additionally, the results of gut microbiota showed that after the intervention, a decrease trend of F/B value and Deferribacterota was noticed in the FH group compared with M group. At the genus level, FAK intervention significantly increased that of Ileiobacterium compared to the M group (p<0.05). A rising trend of norank_f_Muribaculaceae, Lactobacillus and Bifidobacterium were also observed in the HF group. Conclusively, these findings demonstrated that FAK intervention can effectively improve obesity in mice caused by high-fat diet and the potential mechanisms was related to the regulation of serum levels of leptin and IL-27, lipogenesis and lipolysis in adipose tissue and gut microbiota composition.